Dye Ligand Epoxide Chitosan/Alginate: A Potential New Stationary Phase for Human IgG Purification - Diego R. Gondim; Luana P. Lima; Maria C. M. de Souza; Igor T. L. Bresolin; Wellington S. Adriano; Diana C. S. Azevedo; Ivanildo J. Silva (Adsorption Science & Technology)
Cibacron Blue F3GA immobilized as ligand onto epoxide chitosan/alginate composite was prepared and evaluated for the purification of human immunoglobulin G (IgG) isolated from human serum by dye-ligand affinity chromatography. The effect of buffer pH on IgG adsorption, kinetic and isothern adsorption of high-purity IgG were studied by batch adsorption. The adsorption isotherm data were well fitted (using 25 mmol/L sodium phosphate buffer at pH 6.0) by the Langmuir–Freundlich model with a maximum adsorption capacity of 99 mg/g, apparent dissociation constant of 1.2 × 10 −6 mol/L and n equal to 4.86. Fixed-bed experiments were performed using high-purity IgG, achieving a recovery rate of 53%. Human serum diluted ten times was also injected into the column. An enrichment of IgG in the elution fraction with traces of human serum albumin was observed. According to the study results, this material can be applied in the purification of human IgG under optimized conditions.